Clinical Implications of Social Anxiety Disorder (SAD) and its Detection Methods- A Systematic Review - Dian Pitaloka Priasmoro; Yuni Asri (Universitas STRADA Indonesia, 2024)
Background: A common symptom of SAD is significant impairment in interpersonal relationships that can affect various aspects of life as well as daily functioning and lead to decreased quality of life. Individuals with high social anxiety will tend to withdraw from social environments. Purpose: This can eventually lead to loneliness and depression. Therefore, early detection is needed to find a diagnosis early on and prevent the condition from worsening. This review aims to determine the clinical picture in patients with SAD and to find out the instruments that /have been used for clinical enforcement in the field. Methods: We conducted a comprehensive search for full-text articles comprising case reports, case-control studies, cohort studies, and cross-sectional studies published between January 1, 2013, and December 30, 2023. The search encompassed databases such as PubMed, ScienceDirect, SAGE, and Scopus. It's important to note that this review does not delve into other clinical conditions associated with Social Anxiety Disorder (SAD), such as anxiety and depression, as they have been addressed in separate discussions. Additionally, the identification of anxiety and depression is excluded from this review. Results: Out of 78 articles that were screened, only 56 met the eligibility criteria to be selected for further review. The initial steps that need to be taken include 1) defining the research objectives; 2) establishing inclusion criteria; 3) developing a search strategy for data retrieval or study selection; 4) collecting data; 5) assessing the quality of studies; and 6) synthesizing the results. Risk of bias was performed using FEAT principles and reviewers’ discussion. A total of 11 final articles that were reviewed showed a significant correlation between anxiety disorder and detection. Conclusion: As individuals with SAD are large in number, based on this review, early detection is required using methods used by local health regions such as through interviews or clinical symptom assessment. This aims to find cases as quickly as possible and provide appropriate interventions.